Impact investing: A review of the current state and opportunities for development - Burze Yaşar (Istanbul Business Research (IBR), 2021)
United Nations Sustainable Development Goals (SDG) are a universal call for action to protect the planet, end poverty and inequality in the world. Government and philanthropy resources are not sufficient to achieve these goals and financial resources from capital markets must be directed to them. Impact investments are “investments made with the intention to generate positive, measurable social and environmental impact alongside a financial return” and can act as a catalyzer to canalize the needed capital to achieve SDG targets by 2030. This paper investigates this emerging financial paradigm, impact investment. History of impact investment and how it differs from socially responsible investment is presented. Several countries have taken initiatives to develop a regulatory framework to support social enterprise financing. Major actors in the impact investment market are private investors, institutional investors, private foundations, banks, development finance institutions, and nongovernmental organizations. Innovative financial structures are developed among these actors along the risk-return spectrum. Impact investing will thrive if ecosystem actors work against the barriers and use the opportunities well. More academic research and training programs are needed to contribute to the development of the impact investment field.
Keywords: 650; Impact investing; Social finance; Social enterprise; Social enterprise financing